Relating historical variables at first presentation with operative findings at laparoscopy for endometriosis. (October 2014) - Menakaya, Uche; Lu, Chuan; Infante, Fernando; Lam, Alan; Condous, George
<x xml:space="preserve">Abstract</x> Objectives To determine the correlation between historical variables at presentation with the phenotype and location of biopsy proven endometriosis at laparoscopy. Methods Prospective observational study. Consecutive women had laparoscopic surgery following clinical suspicion of endometriosis. Standardised history and clinical examination were taken, and the presenting complaints were evaluated within four subsets of women: (i) primary laparoscopy for endometriosis (ii) previous laparoscopically confirmed endometriosis (iii) biopsy positive for endometriosis and (iv) all biopsies negative for endometriosis. Historical pain variables within the four subsets were compared with disease location and phenotype (superficial, deep infiltrating, endometriomata) at laparoscopy. A stringent P‐value of 0.01 was used as the cut‐off for significance. Results Overall 104 consecutive women were included: mean age 34.3 years, 66/104 (63.5%) had reoperation and 38/104 (36.5%) had primary laparoscopy. 89/104 (85.6%) were biopsy positive for endometriosis, and 11/104 (10.6%) were biopsy negative. Superficial endometriosis was most common phenotype. Site of pain did not correlate with ipsilateral location of disease. Significant correlations included as follows: dyspareunia and endometrioma (P = 0.0009) in women undergoing reoperation; dyspareunia and posterior compartment (P = 0.0086) and lateral compartment (P = 0.0004) disease in women with histology proven endometriosis; left iliac fossa pain and biopsy proven posterior compartment endometriosis (P = 0.0041). Conclusions Although a history of dyspareunia in women with previous endometriosis was significantly correlated with endometrioma, site‐specific locations of pain symptoms did not correlate with ipsilateral locations of endometriosis at laparoscopy. The phenotype – combined deep and superficial endometriosis – was associated with dyspareunia among women with previous history of endometriosis.